Strengthening Islamic Values Through Integration of Local Culture in Islamic Religious Education Materials - Iis Nahwiyah; Fajar Syarif (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2025)
Islamic Religious Education (PAI) has an important role in instilling Islamic values in students. However, in practice, PAI learning is often less associated with local social and cultural realities inherent in students' lives. Integration of local culture into PAI materials is an important strategy to make learning more contextual, meaningful, and close to students' daily lives. Local culture that is full of moral values such as mutual cooperation, tolerance, politeness, and responsibility can be used as an entry point in introducing Islamic concepts. This paper discusses the importance of integrating local culture as a means to strengthen Islamic values in the educational environment. Through a contextual and dialogical approach, PAI learning becomes more inclusive and is able to shape students' characters that are rooted in Islamic values while loving their own culture. In addition, cultural integration also contributes to the preservation of local identity in accordance with Islamic principles. Innovation from teachers and policy support are needed so that this process can run effectively and sustainably. Thus, cultural integration into PAI materials is a strategic step to create education that is inclusive and relevant to the socio-cultural context of students. Collaborative efforts from various parties are needed to overcome existing challenges and optimize the potential of this integration in Islamic Religious Education learning.